Biological and clinical implications of telomere dysfunction in myeloid malignancies. (November 2017) - Kishtagari, Ashwin; Watts, Justin
Telomeres at the ends of linear chromosomes protect the genome. Telomeres shorten with each round of cell division, placing a finite limit on cell growth. Telomere attrition is associated with cell senescence and apoptosis. Telomerase, a specialized ribonucleoprotein complex, maintains telomeres homeostasis through repeat addition of telomere sequences to the 3′ telomeric overhang. Telomere biology is closely related to cancer and normal aging. Upregulation of telomerase or activation of the alternative pathway of telomere lengthening is a hallmark of cancer cells, making telomerase an attractive target for cancer therapeutics. In this review, we will discuss telomere biology and the prognostic implications of telomere length in acute myeloid leukemia, and review exciting new investigational approaches using telomerase inhibitors in acute myeloid leukemia and other myeloid malignancies.